Perceived difficulty of a mathematical task: Do teachers and students have a common view? - Nicchiotti, Bianca; Spagnolo, Camilla (LUMAT-B: International Journal on Math, Science and Technology Education, 2024)
This paper illustrates the first results of a qualitative research investigating the factors which influence students and teachers’ perceived difficulty when approaching and solving a mathematical task. The factors that contribute to increasing or decreasing the perceived difficulty concerning a math task have been predominantly studied with respect to student’s perceived difficulty. We started from factors that characterize students’ perceived difficulty (identified in previous studies) and compared them to the ones expressed by teachers that we have collected, in order to highlight some of the teachers’ beliefs connected to perceived difficulty in mathematics.